2014
DOI: 10.1152/japplphysiol.01142.2013
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant before the first inflation at birth improves spatial distribution of ventilation and reduces lung injury in preterm lambs

Abstract: The interrelationship between the role of surfactant and a sustained inflation (SI) to aid ex utero transition of the preterm lung is unknown. We compared the effect of surfactant administered before and after an initial SI on gas exchange, lung mechanics, spatial distribution of ventilation, and lung injury in preterm lambs. Gestational-age lambs (127 days; 9 per group) received 100 mg/kg of a surfactant (Curosurf) either prior (Surf+SI) or 10 min after birth (SI+Surf). At birth, a 20-s, 35 cmH2O SI was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 39 publications
(71 reference statements)
2
62
1
Order By: Relevance
“…In our study using intubated preterm lambs, we systematically describe the interrelationship between the use of antenatal corticosteroids, exogenous surfactant therapy, and two distinct recruitment strategies applied Unlike previous animal studies of respiratory care at birth (6,(10)(11)(12)15,16,(20)(21)(22)(27)(28)(29)(30), our study involved a large sample size. Pooling all epochs, the use of an OLV stepwise PEEP approach significantly improved C dyn and oxygenation compared to a 30-s 40 cmH 2 O SI.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study using intubated preterm lambs, we systematically describe the interrelationship between the use of antenatal corticosteroids, exogenous surfactant therapy, and two distinct recruitment strategies applied Unlike previous animal studies of respiratory care at birth (6,(10)(11)(12)15,16,(20)(21)(22)(27)(28)(29)(30), our study involved a large sample size. Pooling all epochs, the use of an OLV stepwise PEEP approach significantly improved C dyn and oxygenation compared to a 30-s 40 cmH 2 O SI.…”
Section: Discussionmentioning
confidence: 99%
“…While many previous preclinical studies of lung recruitment administered surfactant before the first inflation (21,36), our current strategy is more clinically applicable. We have recently shown that there is considerable variability in the spatiotemporal behavior of lung mechanics at birth, even in controlled preclinical experiments (6,12,23). Although our choice of SI parameters is based on previous work (9,10,12,20,27,29), it is likely that some of our lambs required a longer SI duration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations